1994
DOI: 10.1046/j.1537-2995.1994.341095026976.x
|View full text |Cite
|
Sign up to set email alerts
|

Atypical reactions associated with use of angiotensin‐converting enzyme inhibitors and apheresis

Abstract: Patients receiving ACE inhibitor therapy who are undergoing therapeutic plasma exchange with albumin replacement solutions are at high risk (100%) for atypical reactions. It is recommended that ACE inhibitors be withheld for at least 24 hours before that procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
0
5

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(78 citation statements)
references
References 10 publications
0
71
0
5
Order By: Relevance
“…1 However, they may cause secondary effects, such as coughing, deterioration of renal function in cases of underlying renal artery stenosis, and, more rarely, angioedema. [2][3][4][5][6][7] In addition, these agents are not very effective in some patients, particularly African Americans, in whom high blood pressure (BP) is associated with low renin levels and a response to salt depletion. 8,9 The development of new classes of antihypertensive agents with different mechanisms of action, therefore, remains an important goal.…”
mentioning
confidence: 99%
“…1 However, they may cause secondary effects, such as coughing, deterioration of renal function in cases of underlying renal artery stenosis, and, more rarely, angioedema. [2][3][4][5][6][7] In addition, these agents are not very effective in some patients, particularly African Americans, in whom high blood pressure (BP) is associated with low renin levels and a response to salt depletion. 8,9 The development of new classes of antihypertensive agents with different mechanisms of action, therefore, remains an important goal.…”
mentioning
confidence: 99%
“…Blockers of the renin-angiotensin system (RAS), either angiotensin I-converting enzyme (ACE) inhibitors or angiotensin II (AngII) receptor type 1 (AT 1 ) antagonists, have proved to be efficient and safe (3). ACE inhibitors cause cough and more rarely angioedema (4)(5)(6), and renal function may deteriorate with both ACE inhibitors and AT 1 receptor antagonists in cases of underlying renal artery stenosis (7)(8)(9). In addition, blockers of the RAS are poorly effective in some patients, especially in African Americans in whom high blood pressure (BP) is accompanied by a low-renin state and is usually responsive to salt-depletion (10,11).…”
mentioning
confidence: 99%
“…One study of 299 consecutive patients undergoing plasmapheresis showed that all 14 patients (100%) receiving ACE inhibitors at the time of plasmapheresis reported these symptoms. 2 In contrast, only 20 (7%) of 285 patients not receiving ACE inhibitors reported these symptoms. Thus, ACE inhibitors should ideally be withheld in patients undergoing plasmapheresis.…”
Section: While Undergoing This Treatment Modalitymentioning
confidence: 99%